Load-carrying mechanism to resist progressive collapse of RC buildings - Qian, Kai (2014)
The slew of high profile engineering calamities in the past decade has demonstrated the disastrous consequence of progressive collapse. However, the low probability of such events actually occurring means it is uneconomical to spend extreme resources to design every building against progressive collapse. A more feasible proposition would be to consider alternative fall-back parameters such as secondary load carrying mechanisms that can help to reduce the severity of the collapse, should it actually occur. However, to date, very limited studies have been carried out to quantify the effectiveness of such secondary load carrying mechanisms in resisting progressive collapse, especially membrane actions developed in RC slabs. Therefore, a series of 6 one-quarter scaled specimens were tested and the failure modes, loaddisplacement relationships, load redistribution responses, and strain gauge results are presented herein. The contribution of each mechanism on the load-carrying capacity is discussed. A series of analyses are also carried out to better quantify the findings made in the study.